The Synthesis of Activated Carbon from Agricultural Residues for Application as an Adsorbent Via Easy Method and Using the Innovative Simple Biomass Incinerator - Leelatam, Tappagorn; Roschat, Wuttichai; Fongwichai, Thanaphon; Tamprasee, Warisara; Phewphong, Sunti; Moonsin, Preecha; Nuengmatcha, Prawit; Suwannarong, Prawit; Promarak, Vinich (Trends in Sciences, 2025)
Activated carbon is widely used in environmental and industrial applications due to its high adsorption capacity. This research aimed to utilize agricultural waste materials—rubber wood twigs, rubber seed pods, Leucaena leucocephala wood, and coconut shells—as precursors for the production of activated carbon, addressing the increasing need for low-cost and sustainable adsorbents. Both dry and wet chemical activation methods were employed using sodium hydroxide (NaOH) in conjunction with a biomass incinerator. Among all the samples, activated carbon derived from rubber wood twigs (AC/rwt) via dry activation demonstrated the most favorable properties. Comprehensive characterization was conducted using X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET) surface area analysis, transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FT-IR). Adsorption efficiency was evaluated through iodine number measurement and methylene blue adsorption tests. The AC/rwt sample exhibited a specific surface area of 726.60 m²/g, an iodine number of 616.73 mg/g, and a methylene blue adsorption efficiency of 99.65 %, which complies with Thailand’s industrial standard TIS 900 - 2004. Elemental analysis confirmed that carbon was the predominant element in all samples. Additionally, the pore size distribution indicated mesoporous structures ranging from 2 - 50 nm. Although commercial activated carbon outperformed in some metrics (950.02 m²/g surface area, 743.77 mg/g iodine number, and 100 % methylene blue adsorption), this study demonstrates that agricultural waste can be successfully converted into high-quality activated carbon suitable for diverse adsorbent applications. HIGHLIGHTS Activated carbon from rubber wood twigs (AC/rwt) has 726.60 m²/g porosity, 616.73 mg/g iodine, surpassing Thai standards. AC/rwt shows 99.65 % methylene blue adsorption, proving effective use of waste for high-performance adsorbents. Though slightly lower than commercial counterparts, AC/rwt meets TIS standards, showcasing agricultural wastes potential for sustainable activated carbon production. GRAPHICAL ABSTRACT